O “triunfo dos mártires” : o discurso emocional na crônica Historia Ecclesiastica, y Flores de Santos de España de Juan de Marieta (1594) - Machado, Joyce Damaris Augusta (2020)
This dissertation aims to analyze the emotional discourse present in the martyrological narrative of the chronicle Historia Ecclesiastica, y Flores de Santos de España of the Dominican friar Juan de Marieta, compiled at the end of the 16th century. To this end, we use the historiographical bias of the History of Emotions, especially the concept of "emotional community" by Barbara Rosenwein, which will lead us to understand the construction of the Spanish Christian identity proposed by Marieta through emotions found in the life narratives of holy martyrs described in the chronicle. The emotions that will be presented compose the norms and emotional conducts of the Christian communities proposed by the chronicler, which allow to legitimize the doctrinal reform promulgated by the council of Trent, to justify the expulsion of Jews and Muslims and to base the union between the monarchy of Phelipe II and the Catholic church.